KAJIAN PEMUPUKAN FOSFOR PADA TIGA TINGKAT STATUS FOSFOR TANAH TERHADAP TANAMAN PADI SAWAH DI KABUPATEN DHARMASRAYA SUMATERA BARAT - Ismon L (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACT Study of P Fertilization on Three Levels of Soil P Status Towards Lowland Paddy Field in the Dharmasraya District, West Sumatra Province. Based on phosphorus (P) status map (1: 250,000), from the total area of paddy soils in West Sumatra (225,165 ha), about 37,389 ha (16.6%) shows low level of P status, while 95,983 ha (42.6%) and 91,793 ha (40.8%) show medium and high P status, repectively. To obtain the specific fertilization rate based on the type of soil, it is necessary to study the effect of P fertilization and its residual effect on the high P status of lowland paddy soil. The research objective was to determine the optimum rate of P fertilizer on the three level of P status of paddy soils (low, medium, high) towards lowland paddy field in the production center area located in Dharmasraya district, which has Typic Hapludults soil type. Research had been done at three locations (low, medium, and high P status). The first planting season tested five levels of P fertilizer rates. The rates were 18, 36, 72, and 114 kg P2O5 per ha in three P status (low, medium, high) using a Randomized Completely Block Design with four replications. Based on the sufficiency and balance of P in the soil, the optimum rates of P fertilizer for each P status (low, medium and high) were 88.58 kg P2O5/ha; 74.86 kg P2O5/ha; and 0 kg P2O5/ha, repectively. Keywords: fertilizer, paddy, phosphorusABSTRAKBerdasarkan peta status fosfor (P) tanah sawah skala 1:250.000, luas lahan sawah di Sumatera Barat yaitu 225.165 ha dengan tingkat kandungan hara fosfor (P) tergolong rendah seluas 37.389 ha (16,6%); sedang seluas 95.983 ha (42,6%); dan tinggi seluas 91.793 ha (40,8%). Untuk mendapatkan dosis pemupukan spesifik lokasi berdasarkan jenis tanah perlu dilakukan penelitian pemupukan P. Tujuan penelitian untuk menentukan dosis optimum pemupukan P pada berbagai status P tanah sawah di kawasan sentra produksi padi sawah Kabupaten Dharmasraya dengan jenis tanah Typic Hapludults. Penelitian dilaksanakan pada tiga lokasi (status P-rendah, P-sedang, dan P-tinggi), menggunakan Rancangan Acak Kelompok dengan empat ulangan. Perlakuan yang diuji pada setiap kelas status hara P adalah lima tingkat takaran pupuk P, yaitu 0, 18, 36, 72, dan 114 kg P2O5/ha dengan 4 ulangan. Hasil maksimum yang dapat dicapai dengan pemberin pupuk P untuk ketiga status P rendah 4.128 kg GKG/ha, P sedang 4.010 kg GKG/ha, P tinggi 4.196 kg GKG/ha. Berdasarkan kecukupan dan keseimbangan hara P dalam tanah, takaran optimum pupuk P untuk masing-masing status P (rendah, sedang dan tinggi) 88,58 kg P2O5/ha; 74,86 kg P2O5/ha; dan 0 kg P2O5/ha. Kata kunci: padi sawah, pemupukan, fosfat